Efficiency of the Austrian disease management program for diabetes mellitus type 2: a historic cohort study based on health insurance provider's routine data - Ostermann Herwig; Hoess Victoria; Mueller Michael (BMC, 2012)
Abstract Background The Austrian diabetes disease management program (DMP) was introduced in 2007 in order to improve health care delivery for diabetics via the promotion of treatment according to guidelines. Considering the current low participation rates in the DMP and the question of further promotion of the program, it is of particular interest for health insurance providers in Austria to assess whether enrollment in the DMP leads to differences in the pattern of the provision of in- and outpatient services, as well as to the subsequent costs in order to determine overall program efficiency. Methods Historic cohort study comparing average annual levels of in- and outpatient health services utilization and its associated costs for patients enrolled and not enrolled in the DMP before (2006) and 2 years after (2009) the implementation of the program in Austria. Data on the use of services and data on costs were extracted from the records of the Austrian Social Insurance Institution for Business. 12,199 persons were identified as diabetes patients treated with anti-diabetic medication or anti-diabetics with insulin throughout the study period. 314 diabetics were enrolled in the DMP. Results Patients enrolled in the diabetes DMP received a more evolved pattern of outpatient care, featuring higher numbers of services provided by general practitioners and specialists (79 vs. 62), more diagnostic services (22 vs. 15) as well as more services provided by outpatient care centers (9 vs. 6) in line with increased levels of participation in medical assessments as recommended by the treatment guideline in 2009. Hospitalization was lower for DMP patients spending 3.75 days in hospital, as compared to 6.03 days for diabetes patients in regular treatment. Overall, increases in costs of care and medication throughout the study period were lower for enrolled patients (€ 718 vs. € 1.684), resulting in overall costs of € 5,393 p.c. for DMP patients and € 6,416 p.c. for the control group in 2009. Conclusions Seen from a health insurance provider's perspective, the assessment of the Austrian diabetes DMP shows promising results indicating improved quality of outpatient care as well as overall cost advantages due to the lower hospitalization rates. Due to methodological limitations of the retrospective study and to the restricted data access, further promotion of the DMP must be accompanied by prospective research and preferably controlled trials in order to provide a solid basis for the decision of whether to include diabetes DMP into the insurer's basic benefit package.